PENERAPAN PUTUSAN BAHTSUL MASA’IL BIDANG EKONOMI DI LINGKUNGAN WARGA NU - Junaidi (Al'Adalah, 2016)
The decision of Bahtsul Masail, as the product of Islamic law, it is expected to be implemented in human’s activities so that it can be achieved peacefully. However, in fact it has inequality between the theory and practice which is done by human. NU society, especially who domiciles in Kaliwates subdistrict , is the society who have a very high adherence to the leader (kyai) or ulama. It can be seen from their attitude when they meet the ulama, moreover they will do what the ulama said. Yet, related to the implementation and application of Bahtsul Masail in economic field, which is also decided by ulama, the respond which is given by NU society is quite varieties. It means that there are some NU society who respects with the decision of Bahtsul Masail in economic field, while others are cannot do that decision.